Development of Pectin-Based Films with Encapsulated Lemon Essential Oil for Active Food Packaging: Improved Antioxidant Activity and Biodegradation - Belkis Akachat; Louiza Himed; Merniz Salah; Maria D’Elia; Luca Rastrelli; Malika Barkat (Foods)
This study evaluated the physicochemical, morphological, and functional properties of pectin-based films incorporated with lemon essential oil (EO) to assess their potential as biodegradable food packaging materials. The results showed that EO incorporation significantly influenced the film’s characteristics. The control film exhibited a smooth surface, while the EO-containing film had a rougher texture with globular structures and interconnected channels, likely representing dispersed EO droplets and matrix alterations. The mechanical analysis revealed increased elongation at break (20.05 ± 0.784%) for EO-incorporated films, indicating improved flexibility, while tensile strength and Young’s modulus decreased, suggesting reduced stiffness. Film thickness increased slightly with EO (0.097 ± 0.008 mm) compared to the control (0.089 ± 0.001 mm), though the difference was not statistically significant (p > 0.05). Moisture content decreased in EO-containing films (28.894%) compared to the control (35.236%), enhancing water resistance. Water solubility increased slightly (16.046 ± 0.003% vs. 15.315 ± 0.040%), while the swelling rate decreased significantly (0.189 ± 0.003 vs. 0.228 ± 0.040; p < 0.05), indicating greater structural stability in aqueous environments due to the hydrophobic nature of EO. Transparency tests showed that EO slightly increased film opacity (0.350 ± 0.02 vs. 0.290 ± 0.012), aligning with trends in UV-protective materials. The EO-incorporated films also exhibited moderate antibacterial activity against Staphylococcus aureus and Escherichia coli. Antifungal tests revealed strong inhibition of Botrytis cinerea (100%) and moderate inhibition of Alternaria alternata (50%) in EO-containing films. These results demonstrate that EO incorporation improves the functional properties of pectin films, enhancing their flexibility, antimicrobial activity, and environmental stability, making them promising candidates for sustainable food packaging applications. These novel active food packaging materials exhibit strong physical properties and significant potential in maintaining food quality and prolonging shelf life.